Phylogeny and revision of Schraderiellus Rider, 1998 with the description of five new species (Hemiptera, Pentatomidae, Discocephalinae, Ochlerini) - Roell, Talita; Campos, Luiz Alexandre (Zootaxa, 2018)
A cladistic analysis of Schraderiellus Rider, 1998 is provided in this study. Were used 60 morphological characters for 34 taxa, including the two known species of Schraderiellus and five new species in the ingroup, two species of Discocephalini and 24 species of Ochlerini in the outgroup, and Euschistus hansi Grazia, 1987 as root. The analysis was made using TNT through heuristic searches under implied weighting of characters. The analysis indicates the monophyly of Schraderiellus with seven valid species. Schraderiellus is redescribed, and five new species are described: S. brevicolis sp. nv., S. falcatus sp. nv., S. luridomaculatus sp. nv., S. luteipedis sp. nv. and S. rufilineatus sp. nv., and a key for the species is presented.